Propofol Regulates the Expression of BecliN-1 through miR-30b and Protects against Lung Ischemia-Reperfusion Injury - Kang, Huanju; Chen, Junjie; Cao, Su (Cellular and Molecular Biology, 2022)
Pulmonary ischemia-reperfusion can cause severe dysfunction of alveolar epithelium and alveolar cells. Drugs such as propofol have a protective effect on lung ischemia-reperfusion, but this protective mechanism is not stable and requires other factors such as nucleosides. The purpose of this article is to study the protective mechanism of propofol on lung ischemia-reperfusion injury by regulating the expression of BecliN-1 by miR-30b. With 72 male rats as the research object, a rat lung ischemia-reperfusion model was established. Phenol agents were perfused as the perfusion solution to detect the expression levels of miR-30b and BecliN-1, statistical experimental data and analyze the regulatory mechanism of miR-30b on the expression of BecliN-1 and the effect of propofol on the protection of lung ischemia-reperfusion. Research results show that propofol can reduce inflammation, reduce oxidative stress, inhibit lung tissue apoptosis, improve lung function and pathological changes of lung tissue by inhibiting the activation of the JAK-STAT signaling pathway, and propofol can pass. The protection of miR-30b’s regulation of BecliN-1 expression against lung ischemia-reperfusion injury is 30% higher than that of other protective mechanisms. At the same time, the apoptosis rate of inflammatory lung tissue cells is reduced by 13%.